Basic gas chromatography-mass spectrometry : principles and techniques - Karasek, Francis W., 1919- (Elsevier ; Distributors for the U.S. and Canada, Elsevier Science Pub. Co., 1988)
The book begins by covering the basic principles of both gas chromatography (GC) and mass spectrometry (MS) to the extent necessary to understand and deal with the data generated in a GC-MS analysis. The focus then turns to the particular requirements created by a direct combination of these two techniques into a single instrumentation system. The data generated and their use are covered in detail. The role of the computer and its specific software receives special attention, especially in the matter of compound identification via mass spectral search techniques. GC-MS-computer instrumentation has reached such a plateau of excellence today that the present commercial systems will not be obsolete for a long time to come. Therefore, a detailed description of these systems is not only informative but is also pertinent to the subject matter of this book. Finally, representative applications and results obtained with GC-MS-computer techniques are presented and chosen in such a way as to permit extrapolation of specific applications to similar problems encountered by the reader. To aid the reader in mastering the subject matter and increase understanding, interpretation problems and suggested readings are included. The format is instructional, informative and application-oriented with material presented in such a way as to be useful to a broad spectrum of people. The book serves as a text in its own right. The software package Gas Chromatography-Mass Spectrometry: A Knowledge Base, by F.A. Settle, Jr. and M.A. Pleva provides rapid access to a wealth of current information in the GC-MS field. Its three diskettes (51/4 inch) allow the user three ways to access: the index mode, the tree mode and a keyword search mode. The package may be purchased separately and is available for the IBM-PC and compatibles. The software provides a valuable supplement to the book.